CORPORATE GOVERNANCE PRACTICES AND EFFECT OF CULTURE OF CEO SUCCESSION PLAN ON BANKS’ FINANCIAL PERFORMANCE IN NIGERIA - Mohammed Shaba; A. O Salami; Mubaraq Sanni (Malete Journal of Accounting and Finance, 2023)
In recent time, good corporate governance has been adjudged to be a basis for the outstanding financial performance of banks in developed and developing economies and this is evident in pre and post consolidation era of Nigerian banks. As such, this study examined the effect of corporate governance on bank’s performance. The study made use of secondary data from Annual reports of Nigerian Banks quoted on Nigeria Stock exchange and harnessed the views of directors and managers of these banks by means carefully designed questionnaire. The study use adopted ex-post facto survey research design and stratified random sampling method was adopted thereby choosing13 out of the entire 22 quoted banks on the stock exchange in Nigeria. The statistical tools used included cross tabulations, mean and correlation analysis. The results showed that CEO succession plan (CSP) has significant effect on financial performance (at P< 0.05). It was discovered that annual strategic retreat (ASR) has significant effect on the bank’s financial performance (at P< 0.05). Study concluded that there is significant level of compliance by the Nigerian banks to the corporate governance code. Study therefore, recommend that banks are encouraged to improve on their level of transparency and financial disclosure in order to be able to enhance their financial performance.